STUDENTS’ VOICE: APPLYING BRAIN-WRITING IN WRITING RECOUNT TEXT - Widya Agustina; Lilies Youlia Friatin (Wahana Pendidikan, 2019)
This study was aimed at finding out thestudents’ perceptions about the implementation of brain-writing in teaching writing recount text.In order to support the data analysis, the writers used the theory from Sadker and Ellen (2007, p. 6)about the steps in implementing brain writing technique in teaching recount text. Furthermore, in conducting this study the writers used qualitative research in which case study was employed to collect the data from participants in this research that was English teacher who taught recount text through brain-writing technique. Moreover, interview was the instrument used by the writers in collecting the data, then the data analyzed qualitatively. Based on the research findingsthe writersconcluded that the teacher did some steps in implementing brain-writing including. Overall, the steps in implementing brain-writing was relevant with the theory from Sadker, Ellen (2007, p. 6).The second conclusion was about student’s perception in implementing brain-writing technique in teaching writing recount text, the writers concluded that the students viewed the teaching-learning process of recount text through brain-writing technique was enjoy activities that not only improve students’ motivation and students’ achievement.Moreover, the writers suggests that the further researcher to investigate students’ difficulties on the use brain-writing technique in teaching writing